Cooperative play: A strategy for increasing environment care of the early childhood - Khoiriyah Khoiriyah; Ika Atniati (Journal of Early Childhood Care and Education (JECCE), 2021)
Environment care is a behavior should belong to children from an early age, because this period is a milestone that will shape and color the development of the next age. One of the strategies to increase awareness and care of for the environment is through a process of habituation with a cooperative play approach. The cooperative play through habituation carried out in this study such as: disposing of trash into its place by playing maze where the children look for trash bins, sort the stages of planting ornamental plants and collage using plants, forming plants with plasticine, and playing colors by stamping and coloring plants. This research aims to describe the efforts to instill and improve an attitude of environment care for children. This research is an action research with 16 children as the subject. In connection with the condition of the Covid-19 pandemic, data was collected through video observations and notes based on documentation of activities. The action was carried out in 2 cycles with the results of 81.25%. The success of children appears where they are able to dispose trash into its place, to conserve plants by watering them, to grow plants, and to save water.